2022
DOI: 10.1101/2022.05.22.492936
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metformin improves glycemia independently of skeletal muscle AMPK via enhanced intestinal glucose clearance

Abstract: SummaryMetformin is an inexpensive oral anti-hyperglycemic agent used worldwide as a first-choice drug for the prevention of type 2 diabetes mellitus (T2DM). Although current view suggests that metformin exerts its anti-hyperglycemic effect by lowering hepatic glucose production, it has been proposed that metformin also reduce hyperglycemia by increasing glucose uptake in skeletal muscle via activation of AMP-activated protein kinase (AMPK). Herein, we demonstrate in lean and diet-induced obese (DIO) male and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Similarly, metformin-induced GLUT1 expression in the colon and ileum, secondary to increased expression of activating transcription factor 4, might also contribute to the metformin-mediated basolateral intestinal glucose uptake in HFD-fed mice 37 . After uptake into enterocytes, glucose anaerobic metabolism resulted in lactate and acetate accumulation in the wall of the small intestine and release into the circulation; this finding is supported by preclinical 37,55,56 (note that ref. 56 is a preprint and has not yet been peer-reviewed) and clinical studies 57 .…”
Section: Boxmentioning
confidence: 76%
See 2 more Smart Citations
“…Similarly, metformin-induced GLUT1 expression in the colon and ileum, secondary to increased expression of activating transcription factor 4, might also contribute to the metformin-mediated basolateral intestinal glucose uptake in HFD-fed mice 37 . After uptake into enterocytes, glucose anaerobic metabolism resulted in lactate and acetate accumulation in the wall of the small intestine and release into the circulation; this finding is supported by preclinical 37,55,56 (note that ref. 56 is a preprint and has not yet been peer-reviewed) and clinical studies 57 .…”
Section: Boxmentioning
confidence: 76%
“…After uptake into enterocytes, glucose anaerobic metabolism resulted in lactate and acetate accumulation in the wall of the small intestine and release into the circulation; this finding is supported by preclinical 37,55,56 (note that ref. 56 is a preprint and has not yet been peer-reviewed) and clinical studies 57 . Intestinal lactate and acetate production establishes a gut-liver crosstalk to blunt hepatic glucose production, possibly through reduction in the activity of the hepatic pyruvate carboxylase by reducing pH in the portal vein (a consequence of increased lactate) and of the hepatic mitochondrial pyruvate carriers 1 and 2 by acetylation (a consequence of increased acetate) 37 .…”
Section: Boxmentioning
confidence: 76%
See 1 more Smart Citation
“…These observations led to the conclusion that, by inhibiting complex I and activating AMPK, metformin promotes glucose uptake in muscle [93] and enhances insulin sensitivity [141]. However, this hypothesis has been challenged by a very recent study on the muscle-specific knockout of AMPKα1/α2 mouse models, where it was shown that lack of AMPK activity in skeletal muscle of lean and diet-induced obese mice does not affect the ability of metformin to lower blood glucose levels or improve whole-body glucose tolerance [142]. Moreover, in T2DM patients rendered normoglycemic with 4 weeks of insulin treatment, metformin had no effect on insulin-stimulated peripheral glucose metabolism [143], suggesting that the ability of metformin to increase insulin-stimulated muscle glucose uptake could be secondary to improved glucose homeostasis and reduction of glucose toxicity rather than due to a direct effect.…”
Section: Muscle As a Target Tissuementioning
confidence: 99%
“…The study indicated that metformin targets PEN2, thereby interrupting the PEN2-ATP6AP1 axis, which disrupts the glucose-sensing pathway to activate AMPK. Another study by Kjobsted et al [13] indicated that in a lean and diet-induced obese mouse model, metformin increased intestinal glucose clearance without involving skeletal muscle AMPK activation. This study also indicated that chronic metformin increases skeletal muscle AMPK activity in type-2 diabetic patients, which is not associated with increased peripheral insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%